THE ROLE OF MASS MEDIA IN THE IMPLEMENTATION OF THE PR (International journal of artificial intelligence, 2024)
The role of mass media in the implementation of Public Information, Awareness, and Relations (PR) is integral to ensuring effective communication between organizations and the public. Mass media serves as a critical platform for disseminating information, raising awareness on important social and political issues, and fostering positive public relations. Through a variety of channels—such as television, radio, print, and digital media—mass media informs, educates, and engages diverse audiences, influencing public opinion and shaping societal behaviors. Furthermore, mass media plays a pivotal role in crisis communication, monitoring public response, and building credibility for institutions. This paper explores the various functions of mass media within the PR framework, highlighting its impact on information dissemination, public awareness, relationship-building, and public opinion formation.